1980
DOI: 10.1021/j100462a023
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion and NMR studies of chloride and bromide ion binding in aqueous hexadecyltrimethylammonium salt solutions

Abstract: A combination of tracer self-diffusion and NMR techniques was used to study mixed solutions of hexadecyltrimethylammonium chloride (C16TAC) and bromide (C16TAB). The degree of counterion association with the micelles, 03x), and the relative strength of counterion binding was obtained from ^Cl and 82Br self-diffusion studies. A slight increase in ¡8Br occurs at the transition from spherical to rodlike Ci6TAB micelles and is markedly greater than ß of ClgTAC solutions at all concentrations. For C16TAC/C16TAB mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 9 publications
(9 reference statements)
1
39
1
Order By: Relevance
“…The nature of the equation is such that algebraic solution of a and lg from the intercept and the slope is not possible. This and similar works [16][17][18][19] have evidenced parallel effects. A conceptual analysis of the utility of Eq.…”
Section: Results and Discussion Arsupporting
confidence: 78%
See 1 more Smart Citation
“…The nature of the equation is such that algebraic solution of a and lg from the intercept and the slope is not possible. This and similar works [16][17][18][19] have evidenced parallel effects. A conceptual analysis of the utility of Eq.…”
Section: Results and Discussion Arsupporting
confidence: 78%
“…Urea is known to have important physicochemical properties, it reduces hydrophobic interaction and also the micellization extents of surfactants [9,10,12,14,[25][26][27][28][29][30]. A few studies on the counterion binding by the ionic-nonionic mixed micelles have recently appeared [16][17][18][19][20][21][22]. Besides this, counterion binding charac-teristics of CTAB-sodium cholate (NaC) and CTAB-NaC1 have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that pure surfactants (both anionic and cationic) can form two kinds of micelles registering two cmc's [3][4][5][6][7][8][9]. Triener and Makayssi [9] have reported it confirmatively from conductance measurements for alkyltrimethylammonium bromides and their binary mixtures and have concluded that the phenomenon of two-cmc formation can be shown for surfactants having alkyl chains containing carbon numbers 16 or more.…”
Section: Introductionmentioning
confidence: 95%
“…Several experimental methods are available to estimate the distributions of ions between these interfaces and the bulk phase, including solubility, conductivity, potentiometric studies and nuclear magnetic resonance, UV/visible and fluorescence spectroscopy. Most of these methods rely on adjustable parameters to describe the measured property of the ion when bound to the interface, monitoring only one component at a time, and some are limited to narrow ranges of solution compositions (Fabre et al 1980;Tanford 1980;Zana 1985).…”
Section: Introductionmentioning
confidence: 99%